Single probe diffuse reflectance spectroscopy to assess the effect of sarcopoterium spinosum treatment on the cerebral tissue properties of ApoE knockout mouse. Issue 2 (3rd November 2020) - Shemesh, David; Rozenberg, Konstantin; Rosenzweig, Tovit; Abookasis, David
Abstract: In this work, diffuse near‐infrared light reflectance spectroscopy based on a single optical probe, contains central single collection fiber surrounded by a circular array of illumination fibers, was used to quantify cerebral tissue properties in ApoE knockout mice following Sarcopoterium spinosum treatment. Sarcopoterium spinosum, also known as Thorny burnet, is a Mediterranean plant widely used as a traditional therapy for the treatment of a variety of pathologies, primarily type 2 diabetes mellitus (T2D). While it's efficacy in the treatment of T2D, and of other components of metabolic syndrome, have already been validated by us, the aim of this study was to investigate the effects of Sarcopoterium spinosum extract (SSE) on dyslipidemia and vascular functions. We utilized ApoE deficient mice (ApoE −/−, Atherosclerosis‐prone apolipoprotein E‐deficient), who have a severe impairment in plasma lipoprotein clearance and thus develop alterations in blood lipid profile and are highly susceptible to atherogenic plaque formation. A total of 34 male mice were divided into five groups representing various genetic, dietary, and treatment configurations. Optical measurements were used to assess changes in diffused reflectance spectra, optical properties (absorption and scattering), and cerebral tissue chromophore contents. Specifically, significant improvement in cerebral hemoglobin level was observed in ApoE KO mice, fed an artherogenic diet (ATD), upon SSE treatment. Biochemical and histological analyses of ApoE −/− ATD mice showed elevated body weight and a high level of blood triglycerides, free fatty acids and cholesterol. In contrast, in SSE treated mice improvement was observed, suggesting beneficial effects of SSE. In ApoE −/− ATD mice group a higher levels of deoxyhemoglobin was monitored indicating that the rate of oxygen release to the tissue is low. This was supported by decrease in oxygen saturation. It was also shown a reduction in water content in the brain of ApoE KO. Mice fed with the atherogenic diet demonstrated increased water content as compared to STD‐fed ApoE KO mice, while SSE administration reversed the effect of the diet. To our knowledge, no such study has been reported before. Abstract : Diffuse near‐infrared light reflectance spectroscopy contains central single collection fiber surrounded by a circular array of illumination fibers together with biological testing have been used to quantify cerebral tissue properties in ApoE knockout mice following Sarcopoterium spinosum treatment. Five mouse groups were studied, representing different genetic, dietary, and treatment conditions. Improvement in cerebral hemoglobin level was observed in mice fed an artherogenic diet upon treatment while brain water content unchanged.